Mapping of schistosomiasis and soil-transmitted helminthiasis in the regions of centre, East and West Cameroon. - Louis-Albert Tchuem Tchuenté; Romuald Isaka Kamwa Ngassam; Laurentine Sumo; Pierre Ngassam; Calvine Dongmo Noumedem; Deguy D'or Luogbou Nzu; Esther Dankoni; Christian Mérimé Kenfack; Nestor Feussom Gipwe; Julie Akame; Ann Tarini; Yaobi Zhang; et al. (Public Library of Science (PLoS), 2012)
BACKGROUND: Schistosomiasis and soil-transmitted helminthiasis (STH) are widely distributed in Cameroon. Although mass drug administration (MDA) of mebendazole is implemented nationwide, treatment with praziquantel was so far limited to the three northern regions and few health districts in the southern part of Cameroon, based on previous mapping conducted 25 years ago. To update the disease distribution map and determine where treatment with praziquantel should be extended, mapping surveys were conducted in three of the seven southern regions of Cameroon, i.e. Centre, East and West. METHODOLOGY: Parasitological surveys were conducted in April-May 2010 in selected schools in all 63 health districts of the three targeted regions, using appropriate research methodologies, i.e. Kato-Katz and urine filtration. PRINCIPAL FINDINGS: The results showed significant variation of schistosomiasis and STH prevalence between schools, villages, districts and regions. Schistosoma mansoni was the most prevalent schistosome species, with an overall prevalence of 5.53%, followed by S. haematobium (1.72%) and S. guineensis (0.14%). The overall prevalence of schistosomiasis across the three regions was 7.31% (95% CI: 6.86-7.77%). The prevalence for Ascaris lumbricoides was 11.48 (95% CI: 10.93-12.04%), Trichuris trichiura 18.22% (95% CI: 17.56-18.90%) and hookworms 1.55% (95% CI: 1.35-1.78%), with an overall STH prevalence of 24.10% (95% CI: 23.36-24.85%) across the three regions. STH was more prevalent in the East region (46.57%; 95% CI: 44.41-48.75%) in comparison to the Centre (25.12; 95% CI: 24.10-26.17%) and West (10.49%; 95% CI: 9.57-11.51%) regions. CONCLUSIONS/SIGNIFICANCE: In comparison to previous data, the results showed an increase of schistosomiasis transmission in several health districts, whereas there was a significant decline of STH infections. Based on the prevalence data, the continuation of annual or bi-annual MDA for STH is recommended, as well as an extension of praziquantel in identified moderate and high risk communities for schistosomiasis.